ANALISIS SIFAT MEKANIK KOMPOSIT LAMINA BERPENGUAT SERAT KACA WOVEN DENGAN MATRIKS UNSATURATED POLYESTER 2504 APT - Naafi' ul Amri; Gaguk Jatisukamto; Sumarji Sumarji (ROTOR, 2019)
Polymer composites has anisotropic properties, if it receives stress from outside it will increase deformation in all directions. This study aims to determine the effect of composites lamina made from woven glass fibers on 2504 APT unsaturated polyester on tensile and flexural strength. The research methodology used is as follows: the process of making composites using the Hand-Lay Up method, the matrix volume fraction Vfm = 69, 39%, the fiber volume fraction Vfs = 30, 38%. The research parameters observed are the x-direction stress (sx) and the y-axis direction strees, (sy). The results obtained are the y-axis, (sy) = 0.8% greater than the x-axis. The flexural strength of the x-axis direction, (sbx) = 57,7% greater than the y-axis direction. The difference in the value of the tensile strength occurs in the number of different fiber bonds, while the flexural strength of the y direction occurs in the fiber lamina which increases more.